A precisão da cirurgia ortognática com placas de titânio personalizadas: revisão sistemática - Figueiredo, Cristiano Elias (2020)
The objective of this work was to do a systematic review to access the precision of orthognathic surgery with customized titanium plates in relation to the outcome of virtual planning. This is a systematic review with a protocol registered in the PROSPERO database, which followed the PRISMA guideline and Cochrane recommendations. Six databases and two gray literature repositories were used as sources of research articles. The research protocol was registered in PROSPERO (CRD42019133769). Descriptive clinical studies that performed orthognathic surgery using custom titanium plates were included. The risk of bias of the selected studies was assessed by “The Joanna Briggs Institute Critical Appraisal tools for use in Systematic Reviews Checklist for Case Series”. Of the 11,916 studies initially identified, 7 met the eligibility criteria and were included in this review. The studies were case series published between 2015 and 2019. Most of the studies (57%) had a low risk of bias, while only one had a high risk of bias. The total sample included 74 patients with 63 bimaxillary surgeries and 11 unimaxillary surgeries. It can be concluded thar all studies showed acceptable precision within previously established clinical parameters. Although the eligible articles assessed the precision of the orthognathic surgery with respect to virtual planning, the wide variability of evaluation methodologies made it impossible to calculate a combined precision measure. Nevertheless, all studies have suggested that the use of custom titanium plates in orthognathic surgery had high precision compared to the outcome of virtual planning.